Towards micromachine intelligence: potential of polymers - Ussia, Martina; Pumera, Martin (Chemical Society reviews, 2022)
Inspired by the increasing desire to mimic the perfection of nature, micro- and nanorobots are triggering increasing interest among the scientific community. The development of such tiny machines that can autonomously perform specific and various tasks at a small scale has reached a high-level of complexity over the last 15 years although the transition from hard to soft self-propelled architectures has had the most profound impact. The use of organic components, such as polymers, is of particular interest to fulfill the lack of biocompatibility and biodegradability of inorganic-based microrobots. Additionally, the combination of self-powered micro- and nanorobots with some macromolecules' ability to be deformed and respond to external stimuli is an important topic. This review aims to critically assess the fundamental aspects of smart machines composed of polymers, examine recent advances in the combined systems at the micro- and nanoscale, and discuss the specific contribution of several polymer families. This review elucidates the role of smart polymers in the expanding field of intelligent micromachines.
Keywords: polymery; Intelligence; inteligence; Polymers; Humans; lidé